Nyayo: Cultural Contradictions in Kenya Rural Capitalism - Abwunza, Judith M. (Anthropologica, 2022)
Post-independence Kenya has not followed the route of some African countries, breaking with the ideology of world capitalism. Indeed, Kenya’s dominant ethos enshrines economic individualism and capital accumulation as central values. Yet Nyayo as a rallying call for development connotes the spirit of love, unity and peace, along with sharing, "the living and activating cement to the fundamental African socialism ... that motivates all actions, including Harambee in action" (Daniel Arap Moi 1986:18). This paper explores the contradictions between the two discourses as they are played out in the lives of rural Kenyans who are attempting to adhere to state edicts that have little relevance to daily economic experience.